Quand les relations sont au cœur du travail des soignants : quels sont les apports de l’image pour comprendre le travail en soins palliatifs ? - Pascal Cesaro; Anne-Marie Arborio (Images du Travail, Travail des Images)
This article examines methods of image gathering employed in order to study care relationships in a palliative care units. It is based on field work which has been continuously done since the 2000s and which is conducted by a film researcher following a recent collaboration with a sociologist engaged in ethnographic research on hospitals. This four-handed reflection begins with bat examining of the right place for observers in the studied situation and then continues with the  assessment of the conditions in which the film attempts to capture the care relationships, in the specific contexte of palliative care. As the film requires the presence of a third party in the relationship between caregivers and patients, who are often at the end of their lives, doesn’t it it produce effects on these relations ? The analysis of a clip in which a caregiver washes a man helps us consider how images may reveal the relationships which develops during practices of care.